Mission culture on the upper Amazon : native tradition, Jesuit enterprise & secular policy in Moxos, 1660-1880 - Block, David, 1945-2021 (University of Nebraska Press, 1994)
Until recently, historians of the Christian missions in the New World have seen missionaries either as saints and martyrs or as brutal disrupters and oppressors. Both the apologists and detractors of mission enterprise have concentrated solely on the missionaries, regarding the native populations either as childlike beneficiaries or as mutely suffering victims. With the growth of ethnohistory as a field of research, new research has sought to reconstruct the situations, the reactions, and the strategies of native groups, thereby seeing the native peoples of the Americas as active agents in their own history. In Mission Culture on the Upper Amazon, David Block describes the formation of a new society in the Moxos region of the Amazon basin, in what is now northern, or lowland, Bolivia. This society began with the arrival of the Jesuits in the region. The mutual synthesis that became Jesuit mission culture followed, with Moxos Indian cultural survival and adaptation continuing after the expulsion of the Jesuits in 1767. With the cataclysmic onset of the rubber boom, the entire region was plunged into a period of severe exploitation and conflict that persists to this day. Block's nuanced treatment of the mission encounter - one extending over a large time period - permits a balanced understanding of the mission enterprise, native response, and the cultural syntheses that ensued.